Infantile angioma. - Bonifazi, E.; Caprio, F. (European Journal of Pediatric Dermatology, 2018)
Angiomas should be included in the chapter of nevi, namely of those skin malformations which are genetically determined but arise during the fetal life, due to factors altering the normal development of the embryo. This is why nevi do not affect all the skin surface, are present at birth or appear early in life and persist for long periods of time or throughout life. (...).